2016
DOI: 10.1007/s11121-016-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Participation in an eHealth, Family-Based Preventive Intervention for Hispanic Youth

Abstract: The Familias Unidas intervention is an efficacious family-based preventive intervention for reducing substance use and other health risks among Hispanic youth. A current randomized controlled trial (RCT) is examining this intervention's efficacy when delivered via the Internet (eHealth). eHealth interventions can overcome logistical barriers to participation, yet there is limited information about the feasibility of these interventions, especially among ethnic minorities. This paper examines participation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 43 publications
3
42
0
3
Order By: Relevance
“…For example, Mauricio found Latina mothers were more likely to drop out early or have declining attendance compared to other participating mothers (though there were no ethnicity differences for participating fathers). Perrino et al (2016) found associations between greater parental Hispanicism and higher participation in family-based interventions designed for Hispanic youth.…”
Section: Factors Related To Participant Engagement and Retentionmentioning
confidence: 89%
See 3 more Smart Citations
“…For example, Mauricio found Latina mothers were more likely to drop out early or have declining attendance compared to other participating mothers (though there were no ethnicity differences for participating fathers). Perrino et al (2016) found associations between greater parental Hispanicism and higher participation in family-based interventions designed for Hispanic youth.…”
Section: Factors Related To Participant Engagement and Retentionmentioning
confidence: 89%
“…Instead, a complex mixture of individual factors (both mutable and more stable), provider, program, and community-level factors synergistically may affect enrollment, engagement, and retention (McCurdy and Daro 2001). While papers in this special issue acknowledge the importance of all of these factors, none of the papers in this special issue empirically test factors at levels other than the individual, with the exception of Perrino et al's (2016) examination of facilitator experience. We posit in this commentary that taking a broader lens on the factors that may predict participant enrollment, engagement, satisfaction, and retention may better identify critical factors in the design and optimization of prevention programs.…”
Section: Factors Related To Participant Engagement and Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…These papers contribute to translation science by addressing the questions, Bwho will come if you build it?^, Bwhy do people come? ', and Bif they do come, how should we measure it?^A bout the Contributing Articles A diverse set of programs are represented by the studies in this issue, including an online, interactive program (i.e., Pathways for African American Success, Murry et al this issue), an e-health intervention with self-paced online and virtual components (Familias Unidas, Perrino et al 2016), group-based, multi-family, in-person programs (Strengthening Families Program, Coatsworth, Hemady, and George, this issue; New Beginnings Program, Berkel et al 2016;Mauricio et al 2017;) and a brief, in-person program that is intended to be tailored and adapted for individual families (i.e., Family Check-Up, Smith et al 2016). Some of these programs include a child and parent or family component (i.e., Pathways for African American Success, Familias Unidas, and Strengthening Families Program), and others only include a parent component (i.e., New Beginnings Program and Family Check-Up).…”
Section: Enhancing Intervention Participation Is a Translational Resementioning
confidence: 99%